Dampak Aktivitas Penambangan Bahan Galian C pada Lingkungan Biofisik dan Sosial Ekonomi Penambang di Kabupaten Bone Bolango - Salahuddin, Andi (Universitas Negeri Gorontalo, 2024)
Bone Bolango Regency is currently experiencing a fairly rapid development process and automatically has an impact on the high demand for material resources, one of which is C excavated material. Currently, there are at least 40 (forty) companies and individuals who have mining activity permits for excavation C covering a mining area of around 360 Ha. This number does not include activities that do not yet have a permit. This, of course, will have an impact on the biophysical and socio-economic environment of miners. Therefore, researchers took 2 sample locations, namely in Owata Village, Bulango Ulu District, and Longalo Village, North Bulango District, considering that both villages have a fairly large mining area of excavation C compared to other villages. Researchers will analyze the perception of mining communities regarding C mining activities and the impacts caused by the biophysical and socio-economic environment. The results of the analysis will be used in formulating local government policy strategies to maximize positive impacts and minimize negative impacts. Miners' perception of C mining activities was obtained through questionnaire results on 50 (fifty) respondents divided into 25 (twenty-five) respondents in Owata Village and 25 (twenty-five) respondents in Longalo Village. The impact is obtained through qualitative methods, namely from primary data such as surveys and interviews and supported by secondary data from related departments. After that, local government policy strategies are obtained through the SWOT analysis method, namely the results of questionnaires on experts. The results of the analysis show the perception of the mining community in Owata Village and Longalo Village regarding mining activities, namely all of them agree with the mining activities of quarry C. They also fully agree if it is stated that mining activities help support daily income which is useful in supporting the cost of their children's education and the need for socialization related to mining activities from the Regional Government. As for miners who disagree if related to arguments that state that mining activities meet safety standards, can trigger conflicts between miners, are required to have health insurance, have a negative impact on the environment, cause floods, landslides and damage to roads, cause cough disease / ISPA and are obliged to mine managers to make efforts to improve the environment. The impact of mining activities in excavation C on the biophysical environment is (i) soil pollution due to oil splatters produced by machines and heavy equipment used, water in the form of decreased / turbid groundwater quality and exceeding the quality standards of COD and BOD criteria which indicate that groundwater has been contaminated with domestic waste, and air in the form of decreased air quality due to dust produced from mining and transportation activities, (ii) The potential for floods and erosion / landslides in the form of increasing intensity of floods and landslides that often occur in mining areas and surrounding areas, while the impact on economic conditions is as a source of economic income by the community and the impact on social conditions is conflict over mining land ownership.Policy strategies that can be taken by the Regional Government of Bone Bolango Regency to minimize the negative impact of mining activities in excavation C are: (i) Determination of mine sites based on identification and inventory of material reserves, (ii) post-mining land reclamation/rehabilitation, (iii) Erosion and flood control through soil and water conservation efforts.